In House Drug Information Library Services: an Experience - Joshi, Anuradha; Gajjar, Bharat; Trivedi, Mayank (Journal of Information and Knowledge, 2010)
Concern about the knowledge on awareness of warnings and adverse effects regarding drugs is a must and essential for a safe health care practice. Drug alert activity aims to ensure that the future health care professionals are more vigilant to prescribe drugs keeping the respective cautions in the mind. The paper presents the details about novel services started at Pramukhswami Medical College (PSMC), India.